PTGS2/GRP78 Activation Triggers Endoplasmic Reticulum Stress Leading to Lipid Metabolism Disruption and Cell Apoptosis, Exacerbating Damage in Bovine Mastitis - Yan Chen; Bo Fang; Xian Liu; Wenkai Bai; Peiwen Liu; Zhiwei Duan; Ting Lu; Quanwei Zhang; Weitao Dong; Yong Zhang (Biomolecules)
Lipoteichoic acid (LTA), an organic acid of Gram-positive bacteria, is closely related to mastitis in dairy cows. This study evaluates the effect of LTA-induced endoplasmic reticulum stress (ER stress) in vitro using MAC-T (mammary epithelial cells) and in dairy cows with mastitis. LTA stimulation significantly increases ER stress and apoptosis-related factors in MAC-T. Further analysis suggests that the increase in ER stress may be associated with interactions involving PTGS2 and GRP78. Protein structural studies indicate a strong interaction between PTGS2 and GRP78. Lipidomics results further demonstrate that LTA disrupts lipid balance in MAC-T cells, affecting lipid metabolism in the endoplasmic reticulum, including PC, PE, TAG, and DAG, thereby exacerbating inflammation and ER stress. In dairy cows with mastitis caused by Gram-positive bacterial infection, damaged epithelial cells, inflammatory cell infiltration, and apoptotic vesicles are observed in affected tissues. In contrast, tissues from healthy cows exhibit regular epithelial cells without inflammatory cells or apoptotic vesicles. Furthermore, a significant ER stress and apoptosis increase is observed in mastitis tissues. This study demonstrates the close association between LTA-induced cell damage and ER stress, contributing to understanding the mechanisms underlying LTA-induced damage and supporting strategies for mastitis prevention and control in dairy cows.